Flexible hydroxyapatite fiber precipitated by urea through a hydrothermal route. Issue 2 (16th March 2017) - Qi, Mei-li; Xiao, Gui-yong; Shokuhfar, Tolou; Lu, Yu-peng
Abstract : Flexible hydroxyapatite fiber (HAF) with high crystallinity is hydrothermally fabricated through the precipitation of urea. By the analysis of field emission scanning electron microscopy, fourier transform infrared spectrometry and X-ray diffraction, a comprehensive composition and morphological characterization of the products is established. The optimal initial pH lies in the range of 3·0–4·0 for synthesizing ribbon-like fibers with lengths larger than 200 μm. The variation in hydrothermal temperatures from 160 to 200°C shows little effect on the constitution of the products, which are all carbonated hydroxyapatite. The formation of HAF is through a fractal growth of two splittings. The HAF paper formed by suction filtration suggests that the obtained HAF is flexible. Also, the phase and morphology transformation of the precursor and the thermal stability of calcium (Ca)–phosphorus (P) fibers are investigated. HAF is formed by the precursor of octacalcium phosphate fibers and is more stable than it. Bone mesenchymal stem cell culture studies indicate that HAF has potential biocompatibility.